2019
DOI: 10.1108/ijopm-03-2019-0207
|View full text |Cite
|
Sign up to set email alerts
|

Managing performance in quality management

Abstract: Purpose The purpose of this paper is to address potential effects of the control element in quality management. First, behavioural theories on how elements of performance management can affect organisational performance are examined. Second, theoretical models on how perceptions of work conditions may impact well-being and performance are considered. Direct and indirect pathways from performance management to productivity/quality are inferred. Design/methodology/approach Matched employee-workplace data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 115 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…The earlier review of extant literature highlighted the paucity of empirical research into the utility of performance review systems in use in contemporary work organizations with a quality orientation. The widespread uneasiness, open resistance (McGregor, 1957), and even rejection or reforming performance review have led both TQM gurus and their advocates (e.g., Bowman, 1994; Deming, 1986; Waldman, 1994a, 1994b) as well as HRM specialists (Cardy & Munjal, 2016; Grote & Grote, 2011; Murphy, 2020; Wilkinson et al, 1998) to call for research examining the compatibility of performance review activities with TQM (see De Menezes & Escrig, 2019; Durairatnam et al, 2021; Vihari et al, 2022). Based on the data from a sample TQM‐driven organizations operating in different branches of manufacturing industry in the UK, we found that the performance review systems of the case organizations functioned in two very different ways with very different implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earlier review of extant literature highlighted the paucity of empirical research into the utility of performance review systems in use in contemporary work organizations with a quality orientation. The widespread uneasiness, open resistance (McGregor, 1957), and even rejection or reforming performance review have led both TQM gurus and their advocates (e.g., Bowman, 1994; Deming, 1986; Waldman, 1994a, 1994b) as well as HRM specialists (Cardy & Munjal, 2016; Grote & Grote, 2011; Murphy, 2020; Wilkinson et al, 1998) to call for research examining the compatibility of performance review activities with TQM (see De Menezes & Escrig, 2019; Durairatnam et al, 2021; Vihari et al, 2022). Based on the data from a sample TQM‐driven organizations operating in different branches of manufacturing industry in the UK, we found that the performance review systems of the case organizations functioned in two very different ways with very different implications.…”
Section: Discussionmentioning
confidence: 99%
“…While some empirical studies (e.g., Bayo‐Moriones & de la Torre, 2022; De Menezes & Escrig, 2019; Lam & Schaubroeck, 1999; Liao et al, 2023; Soltani & Wilkinson, 2020) have touched upon these issues, most work has not gone beyond armchair theorizing (e.g., Cardy & Munjal, 2016; Flamini et al, 2023; Haines et al, 2004) and we contend that we need in‐depth empirical research of performance review systems in use in organizations that espouse a culture of quality. Addressing these issues, this study aims to empirically explore the alignment of different performance review systems with TQM principles, identify potential reasons for any misalignment, and the resulting performance outcomes in a sample of progressive work organizations with a quality orientation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…DeNisi and Smith, 2014; Beer and Micheli, 2018; Baird et al., 2022) for assessments of employee reactions to performance measurement systems and implications. Since outcomes from performance management may be contingent (de Menezes and Escrig, 2019), current knowledge about respective elements may not generalise. As previously argued (e.g.…”
Section: Introductionmentioning
confidence: 99%